ARHGAP21 Acts as an Inhibitor of the Glucose-Stimulated Insulin Secretion Process - Ferreira, Sandra M.; Costa-Júnior, José M.; Kurauti, Mirian A.; Leite, Nayara C.; Ortis, Fernanda; Rezende, Luiz F.; Barbosa, Helena C.; Boschero, Antonio C.; Santos, Gustavo J. (Frontiers in Endocrinology, 2020)
ARHGAP21 is a RhoGAP protein implicated in the modulation of insulin secretion and energy metabolism. ARHGAP21 transient-inhibition increase glucose-stimulated insulin secretion (GSIS) in neonatal islets; however, ARHGAP21 heterozygote mice have a reduced insulin secretion. These discrepancies are not totally understood, and it might be related to functional maturation of beta cells and peripheral sensitivity. Here, we investigated the real ARHGAP21 role in the insulin secretion process using an adult mouse model of acute ARHGAP21 inhibition, induced by antisense. After ARHGAP21 knockdown induction by antisense injection in 60-day old male mice, we investigated glucose and insulin tolerance test, glucose-induced insulin secretion, glucose-induced intracellular calcium dynamics, and gene expression. Our results showed that ARHGAP21 acts negatively in the GSIS of adult islet. This effect seems to be due to the modulation of important points of insulin secretion process, such as the energy metabolism (PGC1α), Ca2+ signalization (SYTVII), granule-extrusion (SNAP25), and cell-cell interaction (CX36). Therefore, based on these finds, ARHGAP21 may be an important target in Diabetes Mellitus (DM) treatment.